Library in Boruca.... a reflection - Sánchez Espinoza, Florybeth (2010)
Based on an analytical exercise, this document presents a reflection on the indigenous communities of Costa Rica and the implementation of information centres in these regions. It also takes into consideration the ways in which these libraries approach their users, that is, how they support teaching and learning processes.